2005
DOI: 10.1097/01.mpa.0000172566.70619.58
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Endocrine Induction by GLP-1 and TGF-?? in the Developing Pancreas

Abstract: We conclude that TGF-beta isoforms have a specific synergistic role with GLP-1 pathway signaling in early pancreatic development, toward endocrine differentiation and away from acinar differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…GLP-1R activation of those cells also affects transforming growth factor-β signaling pathways, resulting in reduced Smad activity that is conducive to endocrine phenotypes (Yew et al, 2004, 2005; Tei et al, 2005). AR42J cells, even without GLP-1R activation, have the potential to be converted into endocrine (Mashima et al, 1996) or exocrine cells (Christophe, 1994) but are negative for islet hormones and their transcripts under usual culture conditions (Zhou et al, 1999b).…”
Section: The Pleiotropic Effect Of Incretin In Pancreasmentioning
confidence: 99%
“…GLP-1R activation of those cells also affects transforming growth factor-β signaling pathways, resulting in reduced Smad activity that is conducive to endocrine phenotypes (Yew et al, 2004, 2005; Tei et al, 2005). AR42J cells, even without GLP-1R activation, have the potential to be converted into endocrine (Mashima et al, 1996) or exocrine cells (Christophe, 1994) but are negative for islet hormones and their transcripts under usual culture conditions (Zhou et al, 1999b).…”
Section: The Pleiotropic Effect Of Incretin In Pancreasmentioning
confidence: 99%
“…Treatment with GLP-1 has been shown to enhance b-cell differentiation in several experimental systems, suggesting additional roles for proglucagon-derived peptides in pancreas development. [34][35][36][37] It is also shown that transgenic overexpression of Pancreatic Polypeptide (PP) in the developing pancreas example, Ngn3 binds directly to the promoters of the b-cellspecific transcription factors b2/NeuroD and Pax4 to promote the differentiation of progenitor cells into the b cell lineage. 24,25 Ngn3 expression is extinguished coincident with the expression of the endocrine hormones that define the endocrine lineages, for example the insulin expression in b cells (Fig.…”
Section: Role Of Ngn3 In Endocrine Cell Differentiationmentioning
confidence: 99%
“…It was reported some time ago that TGFb1 (TGFB1) enhanced the development of endocrine cells from mouse pancreatic fetal cells, with a more pronounced increase in b-and PP-cells (Sanvito et al 1994), and this effect was subsequently reproduced by Tei et al (2005). Another study showed that TGFb2 (TGFB2) induced differentiation of mESCs into Pdx1-expressing endodermal cells (Shiraki et al 2005), but several other growth factors from this family, including TGFa and TGFb1, did not have any significant effect on promoting Pdx1 expression.…”
Section: Tgfb Signaling and The Generation Of B-cells Thementioning
confidence: 99%